Secessionist movements and ethnic conflict debate-framing and rhetoric in independence campaigns - Huszka, Beata (Routledge studies in nationalism and ethnicity, 2014)
This book analyses how national independence movements' rhetoric can inflame or dampen ethnic violence. It examines the extent to the power of words matters when a region tries to break away to become a nation state.